2013
DOI: 10.18388/abp.2013_2007
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterisation of chlorophyllase from leaves of selected Prunus species--a comparative study.

Abstract: Despite senescence-induced chlorophyll depletion in plants has been widely studied, the enzymatic background of this physiologically regulated process still remains highly unclear. The purpose of this study was to determine selected biochemical properties of partially purified fractions of chlorophyllase (Chlase, chlorophyll chlorophyllido-hydrolase, EC 3.1.1.14) from leaves of three Prunus species: bird cherry (Prunus padus L.), European plum (Prunus domestica L.), and sour cherry (Prunus cerasus L.). Seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
(82 reference statements)
1
3
0
Order By: Relevance
“…Kelly, 2016; Ge et al, 2022; Chattopadhyay et al, 2023).The results of this study were consistent with the ndings for green tea leaves(Okazawa et al, 2006;Sytykiewicz et al, 2013;Ozkan and Ersus Bilek, 2015) Okazawa et al(2006). reported that a pH level of 7.5 was optimal for Chlase extraction from green tea leaves.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Kelly, 2016; Ge et al, 2022; Chattopadhyay et al, 2023).The results of this study were consistent with the ndings for green tea leaves(Okazawa et al, 2006;Sytykiewicz et al, 2013;Ozkan and Ersus Bilek, 2015) Okazawa et al(2006). reported that a pH level of 7.5 was optimal for Chlase extraction from green tea leaves.…”
supporting
confidence: 88%
“…reported that a pH level of 7.5 was optimal for Chlase extraction from green tea leaves. Similarly,Sytykiewicz et al(2013) found that the optimum Chlase pH in wheat seedlings ranged from 7.0 to 8.0. Ozkan and Ersus Bilek (2015) reported that the Chlase activity in spinach was highest at pH 7.0.…”
mentioning
confidence: 89%
See 2 more Smart Citations